Flow structures and unsteadiness in hypersonic shock wave/turbulent boundary layer interaction subject to steady jet - Liu, Qiang; Xie, Wei; Luo, Zhenbing; Sun, Mingbo; Cheng, Pan; Deng, Xiong; Zhou, Yan (Acta mechanica Sinica, 2023)
Direct numerical simulations of Mach 6 hypersonic flow over a 34° compression corner subject to steady jet are conducted. Distributions of skin friction coefficient, wall pressure, mean velocity and temperature, boundary layer thickness and Stanton number demonstrate that the flow changes dramatically in the shock wave/turbulent boundary layer interaction area. It is found that the steady jet has no effect on suppressing flow separation unexpectedly, but increases its spatial scale instead. Instantaneous flow structures show that the turbulence amplification can be observed after the application of flow control, and abundant Gortler-like vorticities appear, but the strength of the main shock decreases. Analyzing the wall fluctuating pressure signals using weighted power spectral density, we found an interesting thing. That is, although the low-frequency oscillation phenomenon induced by separation shock is suppressed by the steady jet, wall fluctuating pressure beneath the jet shock is oscillating at a frequency lower than 0.1 u ∞ / δ ref . Results of coherent and intermittency factor reveal that it is related to the backand- forth movement of the jet shock itself.